COMPOSITION OF DIE STEEL 5HVMFS WITH INCREASED WEAR RESISTANCE AND THE SCHEME OF ITS SMELTING WITH USE OF UNDIVIDED SCRAP OF STEELS R6M5 AND 45 - V. N. Fedulov; I. O. Sazonenko (Литьë и металлургия, 2013)
The technological scheme of the new tool steel 5HVMFS smelting by means of electroslag casting method with the use of different combinations of steel scrap of R6M5 and CH5 steels and dressing the chemical composition directly in the bowl and also filling into metal bowl is developed.